Desempenho de alface sob diferentes níveis de salinidade em sistema semi-hidropônico - Aguiar, Karine Alexia Teixeira (2022)
Lettuce (Lactuca sativa L.) is one of the most consumed leafy vegetables worldwide, with consumption favored by the ease of acquisition, nutritional value, flavor and low cost, leading to a need for production in quantity and quality and supply throughout the year. In Brazil, it is the leafy vegetable most cultivated in hydroponic and semi-hydroponic systems, responsible for 80% of the production of these cultivation systems. This culture is demanding in water and sensitive to the salinity of the irrigation water. However, in the Semi-arid region, the scarcity of good quality water leads to the use of brackish water for irrigation that can limit the development of the species. Thus, the semi-hydroponic cultivation helps to control these adverse environmental conditions and provides an increase in productivity and quality of lettuce. In this context, this study aimed to evaluate the effect of the use of saline nutrient solution on the production of curly lettuce cv. Moana, cultivated in a semi-hydroponic system with commercial substrate. The experiment was carried out in a greenhouse in the Agriculture Sector of the Department of Plant Science, of the Federal University of Ceará (UFC), in Fortaleza-CE, installed in a randomized block design, with five replications, with each experimental unit represented by a pot (capacity for 3L) containing a plant. Lettuce plants were submitted to five levels of saline concentrations (electrical conductivities 1,3; 2,0; 2,7; 3,4 and 4,1 dS m-1) and evaluated by growth and physiological parameters, which showed a decreasing quadratic or linear response to saline doses, revealing that irrigation saline nutrient solution above 2,0 dS m-1 reduced plant growth, with more pronounced reductions at 4,1 dSm-1. Lettuce plants are sensitive to salinity in irrigation water, since salinity reduced most of the variables related to growth, phytomass accumulation and physiology as saline levels increased.